(untitled) (Journal Evaluation in Education (JEE), 2023)
Research objective: Research on the analysis of the application of the group investigation learning model on chemical elements and its influence on students’ critical thinking abilities, which aims to see the effect of implementing this model on students’ critical thinking abilities in eastern European countries. Methodology: This research is a descriptive correlational research with a concurrent embedded mix method design . The sample was determined using a purposive sampling technique with expert consideration. Data analysis was carried out to see the effect of implementing the GI model on students’ critical thinking abilities using the Bivariate Pearson test and significance testing using the t test. Main findings: the results of the correlation test between the implementation of the GI model by students and students’ critical thinking abilities were obtained r xy = 0.710. The results of the normality and homogeneity tests show normal and homogeneous data. The results of the significance test obtained t = 5.878 and t table = 2.032 with dk = 34 and α = 0.05. The results of the research prove that the implementation of the group investigation learning model is going well and there is an influence between the implementation of the group investigation learning model and students’ critical thinking skills in chemical elements in eastern European countries. Recent research: This research strengthens the significant influence of the GI model on students’ critical thinking abilities , especially in chemistry lessons.